Dosimetry with 188Re-labelled monoclonal anti-CD66 antibodies - Glatting, G.; Kull, T.; Blumstein, N. M.; Bunjes, D.; Neumaier, B.; Buck, A. K.; Reske, S. N. (Nuklearmedizin - NuclearMedicine, 2006)
Aim: For the therapeutic application of radiopharmaceuticals the activity is determined on an individual basis. Here we investigated the accuracy for a simplified assessment of the residence times for a 188Re-labelled anti-CD66 monoclonal antibody. Patients, methods: For 49 patients with high risk leukaemia (24 men, 25 women, age: 44 ± 12 years) the residence times were determined for the injected 188Re-labelled anti-CD66 antibodies (1.3 ± 0.4 GBq, 5–7 GBq/mg protein, >95% 188Re bound to the antibody) based on 5 measurements (1.5, 3, 20, 26, and 44 h p.i.) using planar conjugate view gamma camera images (complete method). In a simplified method the residence times were calculated based on a single measurement 3 h p.i. Results: The residence times for kidneys, liver, red bone marrow, spleen and remainder of body for the complete method were 0.4 ± 0.2 h, 1.9 ± 0.8 h, 7.8 ± 2.1 h, 0.6 ± 0.3 h and 8.6 ± 2.1 h, respectively. For all organs a linear correlation exists between the residence times of the complete method and the simplified method with the slopes (correlation coefficients R > 0.89) of 0.89, 0.99, 1.23, 1.13 and 1.09 for kidneys, liver, red bone marrow, spleen and remainder of body, respectively. Conclusion: The proposed approach allows reliable prediction of biokinetics of 188Re-labelled anti-CD66 monoclonal antibody biodistribution with a single study. Efficient pretherapeutic estimation of organ absorbed dose may be possible, provided that a more stable anti-CD66 antibody preparation is available.
Keywords: Dosimetry; radioimmunotherapy; treatment planning; anti-CD66; residence time